Genetic risk factors affecting mitochondrial function are associated with kidney disease in people with Type 1 diabetes. Issue 8 (13th April 2015) - Swan, E. J.; Salem, R. M.; Sandholm, N.; Tarnow, L.; Rossing, P.; Lajer, M.; Groop, P. H.; Maxwell, A. P.; McKnight, A. J.; the GENIE Consortium
Abstract Aim To evaluate the association with diabetic kidney disease of single nucleotide polymorphisms (SNPs) that may contribute to mitochondrial dysfunction. Methods The mitochondrial genome and 1039 nuclear genes that are integral to mitochondrial function were investigated using a case (n = 823 individuals with diabetic kidney disease) vs. control (n = 903 individuals with diabetes and no renal disease) approach. All people included in the analysis were of white European origin and were diagnosed with Type 1 diabetes before the age of 31 years. Replication was conducted in 5093 people with similar phenotypes to those of the discovery collection. Association analyses were performed using the plink genetic analysis toolset, with adjustment for relevant covariates. Results A total of 25 SNPs were evaluated in the mitochondrial genome, but none were significantly associated with diabetic kidney disease or end‐stage renal disease. A total of 38 SNPs in nuclear genes influencing mitochondrial function were nominally associated with diabetic kidney disease and 16 SNPS were associated with end‐stage renal disease, secondary to diabetic kidney disease, with meta‐analyses confirming the same direction of effect. Three independent signals (seven SNPs) were common to the replication data for both phenotypes with Type 1 diabetes and persistent proteinuria or end‐stage renal disease. Conclusions Our results suggest that SNPs in nuclear genes that influence mitochondrial function are significantly associated with diabetic kidney disease in a white European population.